2001
DOI: 10.1242/jcs.114.24.4447
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelope defects associated withLMNAmutations cause dilated cardiomyopathy and Emery-Dreifuss muscular dystrophy

Abstract: Nuclear lamin A and C alleles that are linked to three distinct human diseases have been expressed both in HeLa cells and in fibroblasts derived from Lmna null mice. Point mutations that cause dilated cardiomyopathy (L85R and N195K) and autosomal dominant Emery-Dreifuss muscular dystrophy (L530P) modify the assembly properties of lamins A and C and cause partial mislocalization of emerin, an inner nuclear membrane protein, in HeLa cells. At the same time, these mutant lamins interfere with the targeting and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…30 Formation of intranuclear foci had been reported in HeLa cells transfected with the DCM mutant of lamin A N195K. 34 Figure 2 represents a comparison between the wild type lamin A and representative mutanttransfected cells. The transfection efficiency was between 50 and 60% for the wild type construct and between 20 and 25% consistently in the case of the mutants.…”
Section: ■ Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…30 Formation of intranuclear foci had been reported in HeLa cells transfected with the DCM mutant of lamin A N195K. 34 Figure 2 represents a comparison between the wild type lamin A and representative mutanttransfected cells. The transfection efficiency was between 50 and 60% for the wild type construct and between 20 and 25% consistently in the case of the mutants.…”
Section: ■ Resultsmentioning
confidence: 94%
“…The rationale behind our study is understanding how the mutations in the rod domain of the protein influence the overall structure and hence its self-association behavior at the molecular level. Various studies of samples from laminopathy-afflicted patients as well as with ectopic expression of mutant proteins in cultured cell lines ,, have shown the formation of misshapen nuclei with herniations, blebs, intranuclear foci, and aggregates with various sizes and distribution patterns. This can be attributed to the fact that mutations in lamin A could perturb self-association or homotypic interaction, heterotypic interactions with lamin B1 and B2, interactions with NE-associated and nucleoplasmic proteins, and interactions with chromatin in all possible manners.…”
mentioning
confidence: 99%
“…It is also noteworthy that the autosomal dominant LMNA EDMD mutation L530P similarly impacts both LMNA protein isoforms and fails to localize to the nuclear ruptures despite being more mobile than WT [ 77 ], but in contrast with K542N does not lead to progeria. It can be assumed that the complete loss of the Ig-like fold structure and all of its associated interactions, including the LINC complex proteins Sun1/2 [ 95 ] and emerin [ 96 ], caused by the L530P mutation would constitute a loss of function, albeit only impacting one allele, whereas the K542N mutation may only impact interaction with BAF or at least a subset of interactions of the Ig-like fold. It is also possible that the mechanisms that underlie the progeria-associated deficiency in recruitment of A-type lamins to nuclear ruptures is indicative of defects in the BAF-dependent process of nuclear envelope reformation following mitosis which could underlie disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…FRAP studies on transfected cells have shown that some lamin A mutants that cause disease are more mobile in the nuclear envelope than wild-type lamin A ( , ). Emerin is also partly mislocalized to the ER in some cells transfected with plasmids encoding certain lamin A and C mutants ( ). However, emerin appears to be exclusively localized to the nuclear envelope in cells from human subjects heterozygous for dominant A-type lamin mutations examined by immunofluorescence microscopy ( ).…”
Section: Discussionmentioning
confidence: 99%